Transurethral enucleation of large benign prostatic hyperplasia in sodium chloride solution - I. N. Shvarev (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2016)
Background. Transurethral resection is a generally recognized treatment for small to medium-sized benign prostatic hyperplasia (BPH). Numerous original tools are proposed for surgery of large BPH. These include laser (holmium laser enucleation of the prostate) and transurethral (transurethral enucleation with bipolar (TUEB)) enucleation in 0.9 % NaCl solution, which are accompanied by removal of the maximum adenoma tissue volume, short-term recovery, and a substantially fewer early and late complications.Objective: to evaluate the safety and efficiency of TUEB in patients with large BPH.Subjects and methods. TUEB was carried out in 58 patients with large BPH. Their mean age was 64 years. The gland size was ≥ 102 сm3. The residual urine volume in all the patients was more than 100 ml. One year later, the results of treatment were analyzed using the International Prostate Symptom Score (IPSS), Quality of Life (QoL) Questionnaire, as well as from residual urine volume and remaining prostate tissue.Results. The mean time of surgery and enucleation was 90 and 55 min, respectively. The mean volume of removed adenoma tissue was 99 ml. By the end of month 2 following TUEB, there was a progressive reduction in the total IPSS and QoL scores from 35 to 7 and from 5 to 1, respectively, which preserved this trend by the end of a 1-year follow-up. study. The residual urine amount was less than 30 ml. The mean volume of the prostate tissue left was 8.5 сm3 and less than 11.0 сm3. The ultrasound anatomy of the prostatic urethra (transformation of thin-walled spherical TUR defect that is characteristic slit-like one resembles the inverted letter Y) eventually formed by the end of the 1-year follow-up. Stricture of the urethra and contracture of the bladder neck were noted in none of the cases. Conclusion. TUEB is an alternative to open surgery in patients with the enlarged prostate. The use of isotonic NaCl solution as washing fluid allows one to plan longer surgical intervention without fearing water intoxication.